The CDIO-Based curricular framework and guidelines for an obe implementation - Đoàn, Thị Minh Trinh (2016)
In response to outcome-based education (OBE) implementation needs, Vietnam National University-Ho Chi Minh City (VNU-HCM) proposed a solution that involved adapting CDIO approach to systematically reform the curricula of its strategic university departments to provide students with the skills, knowledge, and attitudes desired by relevant stakeholders, and to use the pilot implementation as a means to develop common frameworks for curriculum design and development that can be exported and replicated at universities within VNU-HCM and at other HEIs throughout Vietnam. In this paper we present a curricular framework and guidelines generalized from adaptations of the CDIO Syllabus and the CDIO Standards 1, 2, 3, 7 and 11, that can help HEIs establish and implement an OBE system for engineering as well as non-engineering programs. The curricular framework addresses different levels of detail for program educational objectives and learning outcomes at both program and course levels, therefore enables linking the program components and assessing progression of student skills. The widespread implementation of the curricular framework at universities within VNU-HCM and its effectiveness for outcomes-based curriculum design and development suggest that it has a potential to help accelerate the OBE implementation.